Physiological Characteristics Associated with Fiber Development in Two Naturally Colored Cotton Cultivars. (1st May 2019) - Xiang, Zhang; Pan, Liang P.; Wei, Du M.; Chen, Zhao; Hua, Wei C.; Yuan, Chen; Di, Dong Z.; Hua, Chen D.
Abstract : Core Ideas: The dynamics of cellulose accumulation in colored cotton fiber increased in an S‐shaped curve, which was not asymmetric and could be simulated with Richards' model (R2 > 0.999). Chlorophyll concentrations (estimated by SPAD values) for colored cotton were lower, compared to white cotton, and the degradation rate was relatively faster. This resulted in lower contents of soluble sugar in the boll shell and the subtending leaf. In the boll shell and the fiber, colored cotton had lower ATPase, sucrose invertase, and UDPG‐PPase activities. At 40 DPA, the SS activity for colored cotton was lower than for white cotton. Naturally colored cotton ( Gossypium hirsutum L.) fibers are commercially valuable, but low fiber quality limits their use. This study investigates changes in enzymes' activities and substance contents involved in carbohydrate synthesis to provide a theoretical basis for improving colored cotton fiber quality. Brown cotton Xiangcaimian 2, green cotton Wanmian 39, and white cotton Sumian 9 (control) were used. Fiber cellulose accumulation for Xiangcaimian 2 and Wanmian 39 were lower than the control. Cellulose content was simulated by Richards' equation ( R 2 > 0.999) and follows an "S" pattern—initial slow accumulation 0–10 d post anthesis (DPA), then rapid 10–40 DPA, then slow 40–50 DPA. Maximum accumulation, the cumulative rate parameter, and maximum cumulative rate for cellulose of colored cotton were all lower for control. Further analysis showed SPAD chlorophyll meter readings, soluble sugar content, leaf sucrose invertase activity, adenosine triphosphatase, sucrose synthase, and uridine diphosphate glucose pyrophosphorylase (UDPG‐PPase) activities in colored fiber were lower than control. Results suggest insufficient nutrients for boll and fiber development, resulting in lower fiber quality and boll dry weight in colored cotton. Sucrose synthase and UDPG‐PPase activities in colored fiber were significantly correlated with fiber maturation ( r = 0.884*, r = 0.914*) and fiber strength ( r = 0.895*, r = 0.935*), indicating lower metabolite and enzyme activities in colored cotton reduced fiber quality. Therefore, it appears improving colored cotton fiber quality may require selection efforts to increase photosynthetic capacity in leaves and transportation capacity of carbohydrates in the boll to supply more nutrient during fiber development.